Election Night, 1945 (1945)
1945 1945-1960 "Election Night, 1945" [T0326.jpg], 1945 Clement Attlee at the Labour Party Headquarters, Transport House, Westminster on General Election Night 1945. Arthur Deakin, general secretary of the Transport and General Workers' Union is second left, front row.